2012
DOI: 10.1007/s13391-011-0980-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of piezoresistivity of pentacene channel in organic thin film transistors under mechanical bending

Abstract: In this report, the electrical properties of both pentacene thin-film and pentacene organic thin-film transistors (OTFTs) under static and dynamic bending were investigated. From the responses to the applied static strain, the piezoresistivity coefficient of pentacene thin-film was determined to be 12.5. Significant changes in the field-effect mobility, µ, and the channel current, which were ascribed to the piezoresistivity of the pentacene channel in OTFTs, were observed while other parameters, such as contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…4d . It has been shown that the global bending of organic transistors based on polycrystalline thin films can have different effects in the field-effect mobility 5 6 34 ; therefore, we infer that different local strains in the wrinkled channel have different effects in the field-effect mobility. The main difference is that the distribution of strains in a wrinkled transistor is inhomogeneous; hence, a way to quantify the net strain in a wrinkled channel is required.…”
Section: Resultsmentioning
confidence: 75%
“…4d . It has been shown that the global bending of organic transistors based on polycrystalline thin films can have different effects in the field-effect mobility 5 6 34 ; therefore, we infer that different local strains in the wrinkled channel have different effects in the field-effect mobility. The main difference is that the distribution of strains in a wrinkled transistor is inhomogeneous; hence, a way to quantify the net strain in a wrinkled channel is required.…”
Section: Resultsmentioning
confidence: 75%
“…As a conjugated polymer used for organic electronics, poly­(3-hexylthiophene) (P3HT) has been widely considered for many applications, such as organic light-emitting diodes (OLED) and organic field effect transistors (OFET). , P3HT has also been used as an electron donor with the fullerene derivative ([6,6]-phenyl-C 61 -butyric acid methyl ester, PCBM) in polymer solar cells with a high energy conversion efficiency. , However, at present, its efficiency remains the main issue limiting its photovoltaic device applications, and one of the main factors that restricts the enhancement of efficiency is its low carrier mobility. Previous studies have focused on the synthesis of high-efficiency materials, , photovoltaic device architectures, and operating principles, , but the essential relationship between structure and performance is fundamental to enhance the performance of photovoltaic devices in terms of polymer physics. For conjugated polymers, chain conformation is the basis for macromolecular structure, and a slight change in conformation affects the photophysical properties and electron structures of polymer systems .…”
Section: Introductionmentioning
confidence: 99%
“…As a conjugated polymer used for organic electronics, poly(3hexylthiophene) (P3HT) has been widely considered for many applications, such as organic light-emitting diodes (OLED) and organic field effect transistors (OFET). 1,2 P3HT has also been used as an electron donor with the fullerene derivative ( [6,6]-phenyl-C 61 -butyric acid methyl ester, PCBM) in polymer solar cells with a high energy conversion efficiency. 3,4 However, at present, its efficiency remains the main issue limiting its photovoltaic device applications, and one of the main factors that restricts the enhancement of efficiency is its low carrier mobility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most of the studies reporting efficient OFET sensors relied on capacitive detection [12,13]. On the contrary, mechanical strain effects on the electrical properties of OSC-based sensors have not been reported with thorough investigations and mostly concerned pentacene as an active layer material, which is known to be unstable in ambient conditions [14,15]. Therefore, an evaluation and optimization of mechanical strain effects on the electrical properties of emerging, stable OSCs needs to be addressed to strengthen their uses in either strain sensitivity (sensors) or strain stability (flexible electronics) oriented applications.…”
mentioning
confidence: 99%